Sports Journalism. New Trends and Future Prospects - Rojas Torrijos, José Luis (2014)
Sports journalism stands out as a form of reporting of high social impact due to the universality of sport and also because of its deep-rooted intranational significance. This journalistic field runs through a moment of flourishing where new specialized media in the different platforms were born and thereby a profound transformation in their structures. This kind of journalism has become an innovative and extremely dynamic area, defined by its continuous exploration of new ways of storytelling embracing new digital technologies. This article focuses on some of the latest trends in sports journalism, which are claimed to show the way for the following years like new multimedia, interactives, data journalism or longform features.